Peran Organisasi Profesi Guru Terhadap Fenomena PPPK Yang Dianggap Belum Optimal Dalam Memenuhi Hak Guru - Sitompul, Kristina Pujasari; Simbolon, Nur Anisa; Irshadi, Filza; Gultom, Joshua Hery; Tambunan, Yusna Elfrida; Jamaludin, Jamaludin; Gultom, Wida Bonor (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
The purpose of this policy analysis is to examine some of the prblems associated with teacher management in Indonesia and to define some policy suggestions for managing teachers as professionals to realize the goals of national education. Writing this article using a descriptive qualitative method, using research instruments, namely interviews and documentation, the writing study contains an anlysis of the policy design, existing problems, and evalutation of the policy.